Using Telegram application to promote student engagement in ESP classroom - Pudyastuti, Zusana E.; Sari, Nara; Palandi, Jozua F. (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
This descriptive qualitative study aimed to explore student engagement and student responses towards using Telegram in the ESP classroom. The participants consisted of 66 students from a private university in Indonesia. They were selected using a purposive sampling method. This study was conducted in a fully online mode class. This study also identified various ways in which assignments and student-to-student/teacher-student relationships in online learning environments can trigger student responses. An observation checklist and an interview guideline were used in data collection, and the theory of student engagement as a controlled action was employed in data analysis. The teaching practice of using Telegram in online classes seems to trigger various constructive responses and lively discussions. The discussion activity was mostly initiated by the teacher or the students who intended to ask questions or clarify an idea. This study shows that the use of Telegram in ESP classrooms contributes to a significant increase in students’ engagement, interaction, motivation, and collaboration online. Despite its limitations, Telegram has proven its benefits to be used for improving students' interaction and engagement during language learning. Language learning is more enjoyable for both the students and teachers by incorporating Telegram in the ESP classrooms. In conclusion, this study presents the importance of technology integration in education, which makes learning more effective and empowering.